Ontology and the lexicon : a natural language processing perspective - Huang, Chu-Ren; Cambridge eBooks (Cambridge : Cambridge University Press, 2010)
The relation between ontologies and language is currently at the forefront of natural language processing (NLP). Ontologies, as widely used models in semantic technologies, have much in common with the lexicon. A lexicon organizes words as a conventional inventory of concepts, while an ontology formalizes concepts and their logical relations. A shared lexicon is the prerequisite for knowledge-sharing through language, and a shared ontology is the prerequisite for knowledge-sharing through information technology. In building models of language, computational linguists must be able to accurately map the relations between words and the concepts that they can be linked to. This book focuses on the technology involved in enabling integration between lexical resources and semantic technologies. It will be of interest to researchers and graduate students in NLP, computational linguistics, and knowledge engineering, as well as in semantics, psycholinguistics, lexicology and morphology/syntax.
Fundamental aspects -- Discovery and representation of conceptual systems -- Interfacing ontologies and lexical resources -- Learning and using ontological knowledge.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Natural language processing (Computer science); Semantics; Electronic books